2016
DOI: 10.7150/ijbs.14878
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antileukemia Activity of ZSTK474 on K562 and Multidrug Resistant K562/A02 Cells

Abstract: Chronic myelogenous leukemia (CML) is a malignant hematological disorder mainly caused by the Bcr-Abl tyrosine kinase. While Bcr-Abl inhibitors including Imatinib showed antitumor efficacy on many CML patients, resistance was frequently reported in recent years. Therefore, novel drugs for CML are still expected. ZSTK474 is a specific phosphatidylinositol 3-kinase (PI3K) inhibitor that we identified. In the present study, the efficacy of ZSTK474, alone or in combination with Imatinib, on K562 CML cells as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 37 publications
3
19
0
Order By: Relevance
“…Sui et al [25] reported that activation of the PI3K/Akt/NF-κB pathway promotes P-gp expression, and the inhibition of this pathway reverses P-gp-mediated multidrug resistance. Zhou et al explored the effect of the PI3K-specific inhibitor ZSTK474 on K562/A02 cells and their results showed that ZSTK474 reversed the resistance of K562/A02 cells to ADM and imatinib by downregulating P-gp expression; accordingly, the target of ZSTK474 for CML treatment is PI3K [26]. It can be seen that PI3K activity plays an important role in the regulation of drug resistance in leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…Sui et al [25] reported that activation of the PI3K/Akt/NF-κB pathway promotes P-gp expression, and the inhibition of this pathway reverses P-gp-mediated multidrug resistance. Zhou et al explored the effect of the PI3K-specific inhibitor ZSTK474 on K562/A02 cells and their results showed that ZSTK474 reversed the resistance of K562/A02 cells to ADM and imatinib by downregulating P-gp expression; accordingly, the target of ZSTK474 for CML treatment is PI3K [26]. It can be seen that PI3K activity plays an important role in the regulation of drug resistance in leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…xenograft models (Yaguchi et al, 2006;Zhou et al, 2016), resulting in cell cycle arrest in G1-phase (Kong and Yamori, 2008). Cell cycle arrest is related to modulating the PI3K/Akt signalling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…3D). The in vivo anti-angiogenic effect was attributed to its dual inhibition mechanism: inhibition of VEGF secretion in cancer cells and direct inhibition of PI3K in endothelial cells 96 . In addition, ZSTK474 inhibited migration and invasion of prostate cancer cell PC3, and blocked the phosphorylation of Girdin and production of MMPs, suggesting the anti-metastatic activity 34 .…”
Section: Pi3k Inhibitors Approved or In Clinical Trialsmentioning
confidence: 99%
“…However, acquired resistance after long term treatment of ZSTK474 has been observed, which might be attributed to over-expression of insulin-like growth factor 1 receptor (IGF1R) 95 . In addition, combination with imatinib exhibited synergic antileukemia activity on chronic myeloid leukemia K562 cells as well as adriamycin-resistant K562/A02 cells 96 . ZSTK474 is now under evaluation in phase I/II clinical trials for treatment of solid tumors.…”
Section: Pi3k Inhibitors Approved or In Clinical Trialsmentioning
confidence: 99%